2023
DOI: 10.3390/antiox12020508
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanins Prevent AAPH-Induced Steroidogenesis Disorder in Leydig Cells by Counteracting Oxidative Stress and StAR Abnormal Expression in a Structure-Dependent Manner

Abstract: Testosterone deficiency may increase the risk of sexual dysfunction and the failure of spermatogenesis. Oxidative stress that is derived from the destruction of homeostasis, disease, and exposure to contaminants can damage the steroidogenicity process in Leydig cells, resulting in a reduction in testosterone synthesis. Anthocyanins are a group of innoxious antioxidants widely recognized in food sources, and are an ideal candidate to relieve oxidative stress-related steroidogenesis disorder. However, there is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…16 Rubi fructus protects ovarian health, but the effective components and corresponding mechanisms remain to be elucidated. 42 Researchers have commonly used AAPH to induce cellular senescence, 43 impaired steroidogenesis, 44 and erythrocyte hemolysis 45 brought about by oxidative stress. It is a common generator of free radicals, decomposed into nitrogen and two R˙radicals under heat around 37 °C, producing ROO˙, ROOR radicals, or R-R products by diffusion or reaction with oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…16 Rubi fructus protects ovarian health, but the effective components and corresponding mechanisms remain to be elucidated. 42 Researchers have commonly used AAPH to induce cellular senescence, 43 impaired steroidogenesis, 44 and erythrocyte hemolysis 45 brought about by oxidative stress. It is a common generator of free radicals, decomposed into nitrogen and two R˙radicals under heat around 37 °C, producing ROO˙, ROOR radicals, or R-R products by diffusion or reaction with oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al indicated that anthocyanins prevented 2,2′-azobis(2-amidinopropane)-dihydrochloride (AAPH)-induced steroidogenesis disorder in the Leydig cells by counteracting oxidative stress and StAR abnormal expression. 36 Furthermore, cholesterol will be converted into pregnenolone by cholesterol side chain lyase in the mitochondria, and pregnenolone further enters the endoplasmic reticulum and is converted into steroid dehydrogenation epiandrosterone or androstenedione by Cyp17a1. Thus, Cyp17a1 deficiency will affect the synthesis of gonadal sex steroids such as cortisol, androgen, and estrogen.…”
Section: Discussionmentioning
confidence: 99%
“…Anthocyanins are a group of natural flavonoids widely distributed in various plant sources, including fruits, vegetables, grains, and other botanicals [ 159 ]. Multiple research studies have elucidated the antioxidative properties of anthocyanins and their correlation with enhancements in spermatogenesis processes [ 160 , 161 , 162 , 163 , 164 ]. Notably, cyanidin-3-O-glucoside (C3G) and protocatechuic acid (PCA) have emerged as prominent anthocyanins found in dietary sources, recognized for their robust antioxidant capabilities in supporting male reproductive health [ 159 , 162 , 165 ] and uterine epithelial cells [ 166 ].…”
Section: Role Of Exogenous Antioxidant Supplementation In Relieving H...mentioning
confidence: 99%